Carbothermic reaction characteristics of Indonesian Lateritic Nickel Ore - Sri Harjanto; Reza M., Ulum; Bambang, Suharno (Universiti Malaysia Perlis, 2010)
Organized by School of Materials Engineering & Sustainable Engineering Research Cluster, 1st - 2nd December 2009 at Putra Brasmana Hotel, Kuala Perlis, Perlis.